Animals in the Qur'an - Tlili, Sarra (Cambridge studies in Islamic civilization, 2012)
The Islamic tradition has always held animals in high esteem, deserving the same level of consideration as humans. The Qur'an opines that 'there is not an animal in the earth nor a flying creature flying on two wings, but they are people like you'. This fascinating and highly original book examines the status and nature of animals as they are portrayed in the Qur'an and in adjacent exegetical works, in which animals are viewed as spiritual, moral, intelligent and accountable beings. In this way, the study presents a challenge to the prevalent view of man's superiority over animals and suggests new ways of interpreting the Qur'an. By placing the discussion within the context of other religions and their treatment of animals, the book also makes a persuasive case for animal rights from an Islamic perspective.